Efficient Solvent-free Synthesis of 14 H-Dibenzo[a,j] xanthenes Catalyzed by 2-Hydroxy-5-sulfobenzoic Acid - Hamzeh Kiyani (Science Faculty of Chiang Mai University, 2019)
The use of 2-hydroxy-5-sulfobenzoic acid (2-HSBA) to demonstrate the catalyze one-pot condensation of 2-naphthol with various aldehydes under solvent-free conditions is described. This method can be implemented with a wide variety of readily accessible reagents to provide 14H-dibenzo[a,j]xanthenes as the dye candidates. A significant feature for the present method to the synthesis of 14H-dibenzo[a,j]xanthenes is that the reactions were performed in the absence of solvent and give products in good to high yields. This approach is reasonably priced, and commercially available of the catalyst is also valuable point for the presented procedure.